Pemberdayaan Kesehatan Anak Usia Sekolah : Edukasi Bahaya Rokok Elektrik di Sekolah Indonesia Kuala Lumpur Malaysia - Junaidi, Junaidi; Ratna Said (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The use of e-cigarettes can endanger health, especially the heart, lungs and other diseases. Therefore, youth understanding of the dangers of e-cigarettes is necessary. The aim of this activity is to raise the understanding of young people about e-cigarettes; to help young people better understand the health hazards of e-sigarettes; and to improve the perception of adolescents who believe that e-cigarettes are a safe way to smoke and are one of the right ways to quit smoking. The method of implementation of this dedication uses a discussion that consists of interactive discussion activities and delivery of material. The results of the pre-test study showed that the majority (40.6%) of teenagers are aware of cigarettes and their common dangers, including that they are aware about e-cigarettes and the dangers. The results of the post-test analysis showed a fairly significant improvement in their understanding after the deliberations carried out through the methods of discussion and video playback. In this case, their knowledge about cigarettes and the dangers of cigarettes, and their knowledge of e-cigarettes and their dangers increased to 82.5% This shows that the approach used during this devotional activity is quite effective. Based on this, it was concluded that all participants stated that they were willing and ready to act as mentors of change to quit e-cigarettes.